Kinerja Inspektorat Daerah Kabupaten Solok dalam Melakukan Fungsi Pengawasan - Resky Amalia Desri; Jumiati Jumiati (Policy, Law and Political Research Center, 2022)
This study aims to describe the performance of the Regional Inspectorate of Solok Regency in carrying out its supervisory function, to describe the factors that affect the performance of the Solok Regency Regional Inspectorate in carrying out its supervisory function. This research was processed with qualitative analysis techniques using descriptive methods, and data collection techniques through interviews, observation and documentation. In accordance with the results obtained from research and discussion of the performance of the Solok Regency Regional Inspectorate in the implementation of the supervisory function, it can be seen from: a) supervision program planning, b) policy formulation and facilitation of supervision, c) inspection, investigation and assessment of the performance of regional apparatus, which is still not optimal. The factors that affect the performance of the Solok Regency Regional Inspectorate in carrying out supervision are weak independence, inadequate human resources, and limited availability of facilities and infrastructure